Enantioseparation of Secnidazole by High-Performance Liquid Chromatography Using Amylose-Based Stationary Phase - Ana C. Nascimento; Rafael F. Perna; Marco A. Cremasco; Cesar C. Santana (Adsorption Science & Technology)
The secnidazole, a drug used in hepatic amebiasis, giardiasis and bacterial vaginosis, was enantioseparated on a semi-preparative scale by high performance liquid chromatography (HPLC), using chiral stationary phase (CSP) containing amylose tris (3, 5-dimethylphenyl) carbamate on silica gel (Chiralpak® AD). The experiments were carried out under normal phase conditions and the separation method exhibited very high selectivity and resolutions. The chromatographic parameters and the effects of column temperature on the retention time and selectivity were evaluated. Thermodynamic parameters were obtained from van't Hoff plots, and the elution order of the enantiomers was determined by circular dichorism. The enantiomers of secnidazole were separated under overloaded conditions with a good performance.